The optimal mix of taxes on money, consumption and income - Fiorella De Fiore; Pedro Teles (European Central Bank (ECB), 2002)
In this paper we determine the optimal combination of taxes on money, consumption and income in transaction technology models. We show that the optimal policy does not tax money, regardless of whether the government can use the income tax, the consumption tax, or the two taxes jointly. These results are at odds with recent literature. We argue that the reason for this divergence is an inappropriate specification of the transaction technology adopted in the literature.
Keywords: E31; E41; E58; E62; 330